Crime, reason and history: a critical introduction to criminal law - Norrie, Alan W. (Law in context, 2014)
"It is eight years since the first edition of this book was published. Where relevant, I have sought to update the argument with new case and statute law. I have also developed the analysis, especially in Chapter 3, where a closer link between the two main sections, on motive and intention and indirect intention, is established"--